2021
DOI: 10.3390/ijms22052287
|View full text |Cite
|
Sign up to set email alerts
|

The Cysteine-Rich Peptide Snakin-2 Negatively Regulates Tubers Sprouting through Modulating Lignin Biosynthesis and H2O2 Accumulation in Potato

Abstract: Potato tuber dormancy is critical for the post-harvest quality. Snakin/Gibberellic Acid Stimulated in Arabidopsis (GASA) family genes are involved in the plants’ defense against pathogens and in growth and development, but the effect of Snakin-2 (SN2) on tuber dormancy and sprouting is largely unknown. In this study, a transgenic approach was applied to manipulate the expression level of SN2 in tubers, and it demonstrated that StSN2 significantly controlled tuber sprouting, and silencing StSN2 resulted in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Similarly, in potato, Nahirñak et al [27] reported that StSN1 could interact with StDWF1, affect the interaction of gibberellin, salicylic acid, and brassinolipids, and participate in hormone balance [ 27 ]. In our previous results, no direct interaction was observed between StSN2 and StDWF1 in a yeast two-hybrid experiment, although StSN2 could interact with three peroxidase isoforms involved in peroxidase-regulated lignin synthesis pathways in yeast cells, indicating that StSN2 negatively regulates lignin biosynthesis and hydrogen peroxide accumulation and ultimately inhibits tuber sprouting [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in potato, Nahirñak et al [27] reported that StSN1 could interact with StDWF1, affect the interaction of gibberellin, salicylic acid, and brassinolipids, and participate in hormone balance [ 27 ]. In our previous results, no direct interaction was observed between StSN2 and StDWF1 in a yeast two-hybrid experiment, although StSN2 could interact with three peroxidase isoforms involved in peroxidase-regulated lignin synthesis pathways in yeast cells, indicating that StSN2 negatively regulates lignin biosynthesis and hydrogen peroxide accumulation and ultimately inhibits tuber sprouting [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…During potato storage, tuber sprouting comprises a series of perplexing physiological and biochemical processes [ 22 ]. In recent research, we found that overexpression of StSN2 inhibited tuber sprout growth, while RNAi lines showed accelerated sprout growth [ 12 ]. In the current study, the qRT–PCR results indicate that the expression of StSN2 is highest in FR (short dormancy variety) and the lowest in BS (long-dormancy variety) after harvest (0 days).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The speci c information of the primers is shown in Table 1. The expression data of StSPS family members in the transcriptome and proteome came from our previous research (Li L Q et al 2017;Deng et al 2021). The tissue expression data used for comparison and analysis came from Ensembl Plants (http://plants.ensembl.org/index.html), and the bud eye tissue in this study corresponds to the tuber cortex tissue in the database.…”
Section: Gene Expression Analysis and Enzyme Activity Determinationmentioning
confidence: 99%